Studying the conditions of assembling traction-drive soil-processing aggregates with tractors of traction-energy concept - Adamchuk, V. V.; Bulgakov, Volodymyr; Булгаков, Владимир Михайлович; Булгаков, Володимир Михайлович; Holovach, I. V.; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович (My University, 2018)
At present the appearance of novel energy-saturated tractors of traction-energy concept requires not only new principles of their aggregating but also the method of assembling aggregates on their basis. Aim. To increase the efficiency of assembling soil-processing aggregates with traction and drive working units based on energy- saturated tractors of traction-energy concept. Methods. The study involved the use of the methods of tractor theory, use of machines, field experimental investigations, statistical methods of processing study results, as well as methods of composing programs and numerical computations on PC. Results. The method of assembling soil-processing aggregates with traction and drive working units was suggested on the basis of technical information, available for a wide audience of specialists. Conclusions. The problem of assembling soil-processing aggregates with traction and drive working units on the basis of energy-saturated tractors of tractor- energy concept should be solved with the consideration of the suggested condition of useful power via traction, determined by the friction properties of a tractor, and the power which the tractor can actually transmit via a power take-off shaft or a hydrosystem
Дослідження умов комплектування тягово-проводних грунтообробних агрегатів з тракторами тягово-енергетичної концепції
Исследование условий комплектования тягово-проводных почвообрабатывающих агрегатов с тракторами тягового-энергетической концепции
Keywords: энергонасыщенный трактор; тягово-приводной агрегат; скорость; мощность; комплектование; енергонасичений трактор; тягово-приводний агрегат; швидкість; потужність; комплектування; energy-saturated tractor; traction-drive aggregate; velocity; power; assembling